OUT-OF-HOSPITAL CARDIAC ARREST AND MEASURES OF CARDIOPULMONARY RESUSCITATION IN EMERGENCY MEDICAL SERVICE PANČEVO – ONE-YEAR ANALYSIS - Baba, Ileana (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Out-of-hospital cardiac arrest (OHCA) is the most urgent condition that healthcare professionals are faced with. The measures of cardiopulmonary resuscitation (CPR) are aimed at establishing ROSC (Return of spontaneous circulation). The objectives of this study were to determine the frequency of OHCA, as well as the demographic characteristics of patients. Methods: The research is in the form of a retrospective study in the period 01.01.2022.-31.12.2022. in the Emergency Medical Service Pančevo. The data are taken from the protocols of home visits and calls, and the results were presented by descriptive statistics. Results: In the one-year study, OHCA was reported in 36 patients. The men were in the majority (69.4%), elders at peaked age 70-81 years. The place of the accident is in most cases residence (72.2%) and the bystander is a layperson (77.8%). Basic Life Support (BLS) measures were administered at 13.9%. The dominant initial rhythm is non-shockable at 69.4%, and ROSC is established at 39%. The dispatcher recognized that it was OHCA in 75% of cases. Etiology is mainly cardiovascular in 44.4% of patients. The most frequent occurrences of OHCA were during the afternoon hours, and the highest number of cases occurred in October. Conclusion: Residence as the most common place of occurrence, and a small number of initiated BLS measures, as well as a part of unrecognized OHCA by dispatchers indicate the necessity of educating the population as well as introducing a unique protocol for dispatchers.